FOLCLORE MUSICAL DE ANGOLA. Angola Folk Music Collection of Magnetic Tapes and Discs Vol. I. Povo Quioco. Chokwe People. Lisboa 1961. (International Library of African Music, 1963)
pages: 58-59
Keywords: Folk music; African Music; Angola